Coupled process simulation of cold extrusion and heat treatment distortion of steel shafts: Prozessübergreifende Simulation des Kaltmassivumformens und der Wärmebehandlung von Wellen aus 20MnCr5. Issue 8 (4th August 2016) - Hunkel, M.; Nadolski, D.
Abstract : A simulation study will be presented regarding effects of cold extrusion – a forming process – on heat treatment distortion of a 20MnCr5 (SAE 5120) steel. Therefore, both cold extrusion and heat treatment simulations with transferring the geometry and the stresses from the cold extrusion to the heat treatment were done. The influence of two degrees of deformation, two friction coefficients, and two heat transfer coefficients between workpiece and tool on the heat treatment distortion was studied. Additionally, heat treatment simulations were done regarding only the geometry without transferring the stress (as machined state). Stress relief annealing and case hardening were applied as heat treatment. Finally, the simulated length changes of the shafts were compared with experimentally determined length changes using different lubricants, degrees of deformation, and heat treatments.